Kosovo Social Protection and Health Expenditure Note - World Bank Group (World Bank, Washington, DC, 2019)
Kosovo is one of the poorest countries in Europe, and a growing proportion of the population is at risk for social exclusion and long-term poverty. Overall spending on social protection has increased significantly over recent years, largely because of increases in pensions and war related benefits resulting in increased fiscal pressure. Pensions are a mechanism to substitute income due to a permanent loss of income generating capacity, such as old age or disability and should not be used as a compensatory measure for other reasons. For this reason, in the early 2000s and faced with the impossibility of using contributory pension records to pay pensions, a universal basic pension was introduced in Kosovo.To contain the expansion of pension spending going forward, the government must refrain from introducing new benefits, disallow increasing benefit levels for all but the basic pensions, and pro-rate existing benefits above basic pension levels contingent on funding availability. The expansion of programs targeted at specific population groups have crowded out spending of the social assistance targeted to the poor, which is both low and declining. Increasing programs' coverage and benefit levels and prioritizing the most disadvantaged are key for increasing the effectiveness and equity of social assistance. Public investments in employment promotion and active labor market programs are limited and insufficient to meet Kosovo's labor market challenges. Given that low levels of health spending, including on drugs, is a leading cause of poverty, the social health insurance reform should not only work to improve health outcomes but also to improve financial risk protection, especially for the poor.